Profile of Prescribing COVID -19 Drug Therapy in Inpatients At Jakarta Haji Hospital - harpolia cartika; Harpolia Cartika; Yusmaniar Yusmaniar; Adin Hakim Kurniawan; Fatwa Hasbi; Desi Suryani (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-nCoV-2) the cause of Coronavirus Disease 2019 (COVID-19) was first discovered in Wuhan on December 2019, has spread throughout the world. Each country tries to develop treatment protocol guidelines following the latest research developments to increase the cure rate due to the absence of standard guidelines.The purpose of this research is to knowing the profile of prescribing COVID-19 drug therapy in inpatients at jakarta haji hospital the period September 2020-February 2021. This research is non-experimental with quantitative descriptive study design was taken retrospectively using secondary data in the form of prescription data history of COVID-19 patient visits recorded on the system with sampling techniques that is total sampling. The results showed that in total 387 COVID-19 patients the most were 46-65 years oldwith 198 patients and the mostly malewith 212 patients. The longest duration of treatment was 3-10 days as many as 246 patients and the highest degree of disease was mild to moderate as many as 363 patients The most widely prescribed drugs were Paracetamol (84.37%), Dexamethasone (78.4%), Osetalmivir (74.1%), Heparin (67.81%), Alprazolam (60.27%), Acetylsitein (58 ,12%), Insulin (54.93%), CTM (53.13%), Amlodipine 50.43%, Vitamin C (48.04%), Levofloxacin (35.48%), and Omeprazole (31.98 %). COVID-19 patients at the Jakarta Haji Hospital receive the main therapies, namely vitamins, antibiotics, antivirals, respiratory drugs, gastrointestinal drugs. The suitability of prescribing drug therapy classes based on the guidelines for the management of COVID-19 is 83% and those that are not in accordance with the guidelines are 27%.